2009
DOI: 10.1108/14714170910950830
|View full text |Cite
|
Sign up to set email alerts
|

Towards sustainable construction: promotion and best practices

Abstract: PurposeThe purpose of this paper is to understand what factors best promote or prevent sustainable construction practices and establish the consistency of how sustainability is measured.Design/methodology/approachA literature review considered the impact of the industry to sustainability and identified what action and initiatives are already in place. Through this, the main drivers, barriers, measures and benchmarks were identified. The opinions of building surveying professionals were sought and analysed.Find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
182
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(206 citation statements)
references
References 13 publications
6
182
0
4
Order By: Relevance
“…As stated in related literature as earlier reviewed, sustainability is the ability to sustain the earth's resources while it is being exploited. The areas involved in sustainability are environmental responsibility, social awareness, and economic profitability [4]. It can be clearly seen that there are two parties from each department that do not possess the whole understanding of sustainable concept.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated in related literature as earlier reviewed, sustainability is the ability to sustain the earth's resources while it is being exploited. The areas involved in sustainability are environmental responsibility, social awareness, and economic profitability [4]. It can be clearly seen that there are two parties from each department that do not possess the whole understanding of sustainable concept.…”
Section: Resultsmentioning
confidence: 99%
“…One of them is sustainability is the ability in sustaining the earth's resources while it is being exploited. The areas involved in sustainability are environmental responsibility, social awareness, and economic profitability [4]. In this context, sustainable concept is the idea of maintaining current resources for our future generation although the resources are being used for different purposes.…”
Section: Principle Of Sustainable Developmentmentioning
confidence: 99%
“…However, since pervasively used in working practice, it was considered relevant as interviewers to become familiar with these topics in order to recognize them, and subsequently redirect interviewees to focus on issues linked to specific boundary objects, the interaction between them and their experiences with the aim of teasing out possible relationships relevant to the notion of sustainable construction as examples of standardized packages. Drawing from current literature and 83 questionnaires, Pitt et al [50] rank widely reported drivers and barriers of sustainable construction, highlighting which social, institutional and material actors are seen as more or less challenging ( Figure 4). Next, relevant details regarding institutional and material actors in the Swiss context are provided.…”
Section: Drivers and Barriersmentioning
confidence: 99%
“…Added to this is the unique position of FM as a business support pillar. It suffices to say therefore, that, the concept of sustainable FM is best described in terms of an organization's economic profitability, environmental responsibility and social awareness [13,28].…”
Section: The Concept Of Sustainable Facilities Management [Sfm]mentioning
confidence: 99%
“…There seems to be a wide recognition of the benefits and importance of incorporating sustainability into FM practice [2,3,13,22,23,25,26,[28][29][30], however, studies and literature focusing on the drivers of SFM are very few [2,25,26].…”
Section: Drivers For Sustainable Facilities Managementmentioning
confidence: 99%